Teacher Adaptation to MATATAG Curriculum Reform in Diocesan Grade 7 Mathematics - Ellin Grace Sudaria; Lee Baraquia (Research Synergy Foundation, 2026)
This study explores the experiences of diocesan Mathematics teachers during the pilot implementation of the MATATAG Curriculum in Math 7, focusing the challenges they faced, the adjustments they made, and the support they received. Employing qualitative multiple-case study design, the findings revealed themes under each of the five constructs from the Statement of the Problem: Preparations for Implementation included participation in training, lesson and resource preparation, use of technological platforms, self-directed learning and collaboration; Major Changes in the Curriculum involved revisions in learning competencies, reorganization of content and sequencing, shifts in teaching and assessment focus, and lack of updated instructional resources; Challenges Encountered comprised students’ learning gaps, limited instructional resources, technological connectivity issues, and teachers’ emotional fatigue; Adjustments Made by Teachers included reteaching strategies, creative resource development, flexible teaching approaches, and professional reflective practice; and Support Received During the Transition encompassed institutional support, peer collaboration and mentoring, material and technological support, emotional and moral support. It was concluded that diocesan Mathematics teachers demonstrated commendable adaptability during the implementation of MATATAG Math 7 implementation. It was recommended that teachers should receive continuous training, sufficient materials, and stronger administrative support to sustain meaningful reforms in Mathematics education.